Immunomodulatory effects of a short-term gluten-free diet on pediatric celiac disease: findings from a single-cell transcriptomics study. - Martin‐Masot, Rafael; Correa-López, Nerea; Herrador-López, Marta; Navas-López, Víctor Manuel; Carmona, Francisco David; Nestares, Teresa; Bossini-Castillo, Lara (Elsevier, 2025)
Celiac disease (CD) is an autoimmune disorder with a strong genetic component, triggered by gluten ingestion. Although a Gluten-Free Diet (GFD) is the standard treatment, its short-term effects on immune cell modulation in pediatric CD remain largely unexplored. This study aimed to investigate transcriptional changes in peripheral blood mononuclear cells (PBMCs) of pediatric CD patients following a strict GFD for 9–10 months, using single-cell RNA sequencing (scRNA-seq). An observational longitudinal study was conducted on five pediatric CD patients pre-GFD and post-GFD (confirmed by gluten immunogenic peptide determination in feces). PBMCs were analyzed using droplet-based scRNA-seq to identify cluster markers and differentially expressed genes (DEGs) between pre-GFD and post-GFD cells. Nineteen immune cell clusters encompassing a variety of classical immune cell subtypes were identified. Key findings included the downregulation of pro-inflammatory genes and the upregulation of immune-regulatory genes after a GFD in different immune cell subsets. Changes in macrophages and monocytes suggested improved immune balance, while T cells demonstrated a shift towards reduced effector activity. Notably, post-GFD regulatory T cells transitioned into a trajectory towards enhanced immunosuppressive profiles, as evidenced by increased HLA-G and decreased DDX5 expression. A strict short-term GFD induced significant immune modulation in pediatric CD patients, highlighting potential biomarkers for disease monitoring. Nevertheless, due to the small sample size, results should be interpreted with caution, and larger cohort studies are needed for further confirmation and validation. These findings provide insights into the immunological mechanisms of GFD and suggest avenues for non-invasive diagnostic strategies to enhance patient management.
Keywords: Enfermedad celíaca en niños; Secuenciación de ácidos nucleicos; Respuesta inmune - Regulación; Células T; Pediatría; Dietas sin gluten; Single-cell RNA-seq; Celiac disease; Pediatrics; Gluten-free diet; Regulatory T cells